Hábitos y creencias en salud oral de la comunidad indígena adulta, en el área rural y urbana del municipio de solano Caquetá- Colombia en el 2019. - Ante Ramos, Yamiled; Cortinez Gutierrez, Angela Vanesa (Universidad Antonio Nariño, 2021)
Identify beliefs, in oral health in these communities, Know the habits in oral health in these communities likewise identify gaps in habits used, and guide this community through education; expanding the variety of knowledge improving their hygiene and oral health, taking into account that the alterations produced in the oral cavity are mainly associated with the little use of elements of oral hygiene and their disinformation. The beliefs in medicinal plants and rituals for the healing of these communities are the pillar of this society, but it is not a benefit that they can receive through these acts, since scientifically speaking, caries or periodontics tend to form from the same way on anyone.